The Clinical Characteristics and Gene Mutations of Maturity-Onset Diabetes of the Young Type 5 in Sixty-One Patients - Ge, Shenghui; Yang, Mengge; Cui, Yuying; Wu, Jing; Xu, Lusi; Dong, Jianjun; Liao, Lin (Frontiers in Endocrinology, 2022)
Aims Maturity-onset diabetes of the young type 5 (MODY5), a rare disease, is very easy to be misdiagnosed as type 2 diabetes. To get better understanding of the disease, we analyzed the clinical characteristics and gene mutations of MODY5. Methods PubMed, Cochrane, the China National Knowledge Infrastructure, and Wanfang were searched with the following search terms: “MODY5” OR “HNF1B maturity-onset diabetes of the young” OR “maturity-onset diabetes of the young type 5” OR “renal cysts and diabetes syndrome”. Clinical characteristics and gene mutations of MODY5 were analyzed. The demography, clinical characteristics, and blood indicators of patients were described utilizing simple summary statistics. Variables were analyzed by t-test, Wilcoxon signed rank test, and Fisher exact test. Spearman’s correlation analysis was used for bi-variate analysis. All tests were two-sided, and a p-value < 0.05 was considered statistically significant. Statistical analysis was performed using the Statistical Package for the Social Sciences version 26 for Windows (SPSS). Results A total of 48 literatures were included in this study, including 61 eligible patients and 4 different mutations. Of the 39 patients with available body weight index, 15 (38.46%) were underweight, 21 (53.85%) were normal weight and 3 (7.69%) were overweight or obese. Of the 38 patients with available family history, 25 (65.79%) reported a family history of diabetes. Of the 34 patients with available age of diabetes diagnosis, the median age of diabetes diagnosis was 16.00 years old and 88.24% (30/34) of patients were under 25 years old when they were first diagnosed with diabetes. Renal cysts were presented in 72.41%, hypomagnesemia in 91.67%, and pancreatic dysplasia in 71.88% of the patients. Patients with hepatocyte nuclear factor 1B (HNF1B) deletion had lower serum magnesium, serum creatinine, and higher eGFR than patients with other gene mutations, and the difference was statistically significant. Conclusions The young onset of diabetes with low or normal BMI, renal cysts, hypomagnesemia, and pancreatic dysplasia should be recommended to genetic testing in order to differentiate MODY5 from other types of diabetes earlier.